Improving Elementary Students’ Mathematical Understanding and Independent Learning Through the Puzzle Learning Media - Yanti Setiawati; Nuril Huda; Muhajir; Soubar Isman (JURNAL PENDIDIKAN DAN PENGEMBANGAN MANUSIA, 2026)
Innovative and engaging instructional media are increasingly required to enhance students’ conceptual understanding and promote learner autonomy in elementary education. Within mathematics learning, game-based media such as puzzles have been suggested as effective tools to support constructivist learning processes. This study aims to examine the effectiveness of puzzle-based learning media in improving conceptual understanding and learning independence among fifth-grade students at Petapan 2 Primary School. A quantitative research design was employed using a saturation sampling technique involving 60 students from classes V-C and V-D. Data were collected through a mathematical understanding test and a learning independence questionnaire. Data analysis was conducted using IBM SPSS version 21 for Windows, including validity, reliability, normality, and homogeneity tests. Hypothesis testing was performed using an independent samples t-test. The results indicate a significant difference between the experimental group using puzzle media and the control group using conventional media. The significance values for conceptual understanding and learning independence were both 0.000 (< 0.05). These findings demonstrate that puzzle-based media significantly enhance students’ mathematical understanding and foster independent learning. Therefore, the integration of constructivist, game-based learning media is recommended to strengthen both cognitive and affective outcomes in elementary mathematics education